Credence Goods Markets and the Informational Value of New Media: A Natural Field Experiment - Rudolf Kerschbamer; Daniel Neururer; Matthias Sutter (Institute of Labor Economics (IZA), 2019)
Credence goods markets are characterized by pronounced informational asymmetries between consumers and expert sellers. As a consequence, consumers are often exploited and market efficiency is threatened. However, in the digital age, it has become easy and cheap for consumers to self-diagnose their needs using specialized webpages or to access other consumers' reviews on social media platforms in search for trustworthy sellers. We present a natural field experiment that examines the causal effect of information acquisition from new media on the level of sellers' price charges for computer repairs. We find that even a correct self-diagnosis of a consumer about the appropriate repair does not reduce prices, and that an incorrect diagnosis more than doubles them. Internet ratings of repair shops are a good predictor of prices. However, the predictive valued of reviews depends on whether they are judged as reliable or not. For reviews recommended by the platform Yelp we find that good ratings are associated with lower prices and bad ratings with higher prices, while non-recommended reviews have a clearly misleading effect, because non-recommended positive ratings increase the price.
Keywords: C93; D82; 330; credence goods; fraud; information acquisition; internet; field experiment